A fireproof and heat-insulating cable material and a preparation method thereof

CN122917427APending Publication Date: 2026-10-16武汉星火电线电缆有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611237155.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]有鉴于此,本发明的目的在于提出一种隔热防火电缆料及其制备方法,以解决现有乙烯基弹性体电缆料难以兼顾挤出弯曲所需柔韧性与受火后残留层的完整隔热性,限制其在高防火电缆中的稳定应用的问题

Benefits of technology

本发明以乙烯-醋酸乙烯酯共聚物构成乙烯基弹性体连续相,使电缆料保持适于挤出成型和弯曲敷设的柔韧性;乙烯-丙烯酸乙酯-马来酸酐三元共聚物经3-氨丙基三乙氧基硅烷牵系端羟基聚二甲基硅氧烷,可减少游离硅氧组分迁移,并改善其与基体及无机填料的相容状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917427A_ABST
    Figure CN122917427A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of cable material, in particular to a kind of heat-insulating fireproof cable material and preparation method thereof.The cable material includes ethylene-vinyl acetate copolymer as the base of ethylene-based elastomer, modified elastic intermediate, aluminium hydroxide, quartz powder, long acicular wollastonite, antioxidant and zinc stearate.The elastic intermediate is made by boronizing ethylene-ethyl acrylate-maleic anhydride terpolymer with terminal hydroxyl polydimethylsiloxane, and then by boric acid partial boronization;Each component is subjected to internal mixing, extrusion and pelletizing to obtain the cable material.The obtained material has flexibility, flame retardancy and heat-insulating integrity, and is suitable for cable insulation layer, sheath layer and fireproof protective layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable material technology, specifically to a heat-insulating and fire-resistant cable material and its preparation method. Background Technology

[0002] When cables are used in buildings, rail transit, and industrial equipment, the insulation, sheath, or fire-resistant protective layer should not only inhibit combustion but also form a stable residual layer at high temperatures to delay heat transfer to the conductor and adjacent lines. Cable materials based on vinyl elastomers such as ethylene-vinyl acetate copolymers are characterized by their softness, ease of extrusion, and good low-temperature adaptability. However, the organic segments are prone to softening, decomposition, and shrinkage when heated, making it difficult to simultaneously maintain flame retardancy and structural integrity.

[0003] Existing technologies typically add aluminum hydroxide to improve flame retardant properties, but higher filler amounts reduce the ductility and melt flowability of vinyl elastomers and cause stress concentration at the filler interface. The residue particles after aluminum hydroxide decomposition have limited cohesion and are prone to pulverization and cracking upon exposure to fire, making it difficult to form a complete and sustainable heat-insulating barrier.

[0004] To enhance the residual layer, existing systems also incorporate quartz powder, needle-like wollastonite, siloxanes, or boron-containing compounds. Insufficient interfacial bonding of inorganic fillers can impair room-temperature tensile properties. Free siloxanes are prone to migration or precipitation, and direct blending of boron-containing components may result in uneven distribution or excessive restriction of chain segment movement, causing a trade-off between flexibility, processability, and high-temperature residual layer strength.

[0005] Therefore, the technical difficulties faced by existing vinyl elastomer cable materials are: while being suitable for extrusion molding, bending installation and long-term use, it is difficult to take into account room temperature ductility, fire-damaged residual layer integrity and thermal insulation stability, which limits their application in cable insulation, sheathing and fire protection layers. Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a heat-insulating and fire-resistant cable material and its preparation method, so as to solve the problem that existing vinyl elastomer cable materials are difficult to balance the flexibility required for extrusion bending and the integrity of the residual layer after fire, thus limiting their stable application in high fire-resistant cables.

[0007] To achieve the above objectives, the present invention provides a heat-insulating and fire-resistant cable material, comprising the following raw materials in parts by weight: 105-115 parts of ethylene-vinyl acetate copolymer; 15-25 parts of modified elastic intermediate; 30-34 parts aluminum hydroxide; 46-50 parts of quartz powder; 14-18 parts of long needle-shaped wollastonite; 0.5~0.8 parts of antioxidant 1010; 0.8~1.2 parts zinc stearate.

[0008] The method for preparing the modified elastic intermediate includes: First, the ethylene-ethyl acrylate-maleic anhydride terpolymer was reacted with 3-aminopropyltriethoxysilane, and then condensed with hydroxyl-terminated polydimethylsiloxane under the catalysis of tetrabutyl titanate. The resulting reaction product was collected independently by precipitation, washing and drying to obtain the modified elastic precursor. The modified elastic precursor is subjected to a borylation reaction with boric acid, and the resulting reaction product is subjected to hot filtration, precipitation, washing and drying to obtain the modified elastic intermediate.

[0009] Preferably, the mass ratio of the ethylene-ethyl acrylate-maleic anhydride terpolymer, 3-aminopropyltriethoxysilane, hydroxyl-terminated polydimethylsiloxane, and tetrabutyl titanate is 90:1.7~1.9:36~40:0.12~0.16.

[0010] Preferably, the amount of boric acid used is 0.18 to 0.32 parts based on 60 parts of the modified elastic precursor.

[0011] Preferably, the preparation of the modified elastic precursor includes: dispersing the ethylene-ethyl acrylate-maleic anhydride terpolymer in anhydrous xylene, stirring for 35-45 min under nitrogen protection, at 95-105°C and 320-380 r / min; adding the 3-aminopropyltriethoxysilane within 15-25 min, and continuing the reaction for 2-3 h; adding hydroxyl-terminated polydimethylsiloxane and tetrabutyl titanate, raising the temperature of the reaction system to 108-112°C within 25-35 min, reacting under a nitrogen flow for 3.5-4.5 h, and then extracting the ethanol fraction.

[0012] Preferably, the vinyl acetate mass fraction in the ethylene-vinyl acetate copolymer is 27%~29%, and the melt mass flow rate of the ethylene-vinyl acetate copolymer at 190°C and 2.16 kg is 5~7 g / 10 min.

[0013] Preferably, the ethylene-ethyl acrylate-maleic anhydride terpolymer has a mass fraction of 27%~31% ethyl acrylate and a mass fraction of 1.1%~1.5% maleic anhydride, and the melt flow rate of the ethylene-ethyl acrylate-maleic anhydride terpolymer at 190°C and 2.16 kg is 5~9 g / 10 min.

[0014] Preferably, the kinematic viscosity of the hydroxyl-terminated polydimethylsiloxane at 25°C is 45~85 mm. 2 / s, number average molecular weight is 2000~3500, hydroxyl mass fraction is 0.9%~1.2%, and hydroxyl equivalent is 0.53~0.70 eq / kg.

[0015] Preferably, the aluminum hydroxide is fine-grained precipitated aluminum hydroxide without organic surface treatment, and the median particle size d50 of the aluminum hydroxide is 1.7~2.1μm, and the BET specific surface area is 3~5m². 2 / g.

[0016] Preferably, the quartz powder is crystalline silica powder without organic surface treatment, wherein the silica mass fraction in the quartz powder is not less than 99.0%, and the particle size d10 is 3~5μm, d50 is 20~26μm, and d90 is not higher than 65μm.

[0017] Preferably, the long needle-shaped wollastonite is long needle-shaped wollastonite without silane surface treatment, with an average particle size of 9~12μm, an aspect ratio of 10:1~20:1, a silica mass fraction of 46%~54%, and a calcium oxide mass fraction of 43%~50%.

[0018] Preferably, the antioxidant 1010 is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], with a purity of not less than 98.0%, a melting point of 110~125℃, and a volatile content of not more than 0.50%; Preferably, the zinc stearate has an ash content of 12.8% to 14.2%, a free fatty acid content of no more than 1.5%, a moisture content of no more than 0.5%, and a melting point of 118 to 125°C.

[0019] This invention also provides a method for preparing heat-insulating and fire-resistant cable material, comprising the following steps: (1) Add the ethylene-vinyl acetate copolymer to a mixer for plasticizing, add the modified elastic intermediate, and continue mixing to obtain a polymer mixture; (2) Aluminum hydroxide, quartz powder, long needle-shaped wollastonite, antioxidant 1010 and zinc stearate are premixed evenly, the resulting premix is ​​divided into 3 equal parts and added to the polymer mixture in sequence, and after further mixing, the mixture is discharged to obtain the mixture. (3) The mixture is fed into a co-rotating twin-screw extruder for melt extrusion. The extruded strip is cooled and pelletized to obtain the heat-insulating and fire-resistant cable material.

[0020] Preferably, in step (1), the set temperature of the internal mixer is 90~100℃, the rotor speed is 45~55r / min, the plasticizing time of the ethylene-vinyl acetate copolymer is 2~4min, and the mixing time after adding the modified elastic intermediate is 3~5min.

[0021] Preferably, in step (2), the feeding interval between two adjacent premixes is 1-2 min, the mixing time after the third premix is ​​added is 6-10 min, and the material temperature at discharge is 118-122℃.

[0022] Preferably, in step (3), the temperatures of the four barrel temperature zones of the co-rotating twin-screw extruder are 100~110℃, 110~120℃, 120~130℃ and 120~130℃ respectively, the screw speed is 70~90r / min, and the feed rate is 2~3kg / h.

[0023] Preferably, in step (3), the extruder is air-cooled and then pelletized, and the pellets that pass through a 4mm sieve and remain on a 2mm sieve are collected.

[0024] The beneficial effects of this invention are: This invention uses an ethylene-vinyl acetate copolymer to form a continuous phase of vinyl elastomer, which enables the cable material to maintain flexibility suitable for extrusion molding and bending installation; the ethylene-ethyl acrylate-maleic anhydride terpolymer is linked to hydroxyl-terminated polydimethylsiloxane by 3-aminopropyltriethoxysilane, which can reduce the migration of free silicon and oxygen components and improve its compatibility with the matrix and inorganic fillers.

[0025] The terminal hydroxyl siloxane chain is partially boronized with boric acid, which forms a boron-containing connection structure while retaining the flexibility of the siloxane chain. This makes it easier to maintain the connection between the residual phases when the material is heated, reducing the tendency of the residual layer to loosen and crack, thus balancing room temperature ductility and high temperature structure retention.

[0026] Aluminum hydroxide absorbs heat and releases moisture when heated, quartz powder replenishes the high-temperature resistant inorganic phase, and long needle-shaped wollastonite provides skeletal support. Together with some borosilicate chains, these three components promote the formation of a continuous heat-insulating residual layer, which helps to delay the transfer of heat to the inside of the cable.

[0027] Antioxidant 1010 can reduce thermal and oxygen damage during processing, and zinc stearate helps improve filler dispersion. The resulting vinyl elastomer cable material is suitable for insulation, sheathing and fire protection layers. Compared with the system of direct blending of free silicon oxygen components and boron-containing components, it is more conducive to taking into account processability, flexibility, flame retardancy and fire insulation performance.

[0028] This solution uses copolymers to bind and partially borohydride silica chains, combined with aluminum hydroxide, quartz powder, and long needle-like wollastonite, to enable vinyl elastomer cable materials to form a continuous and robust fire-resistant insulating residue layer while maintaining extrusion processing and bending flexibility. Compared to existing systems that directly blend free siloxanes and boron-containing components, it exhibits lower component migration and residue layer loosening tendencies, making it suitable for cable insulation layers, sheathing layers, and fire-resistant protective layers. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Figure 1 This is a flowchart illustrating the preparation process of heat-insulating and fire-resistant cable materials.

[0030] Figure 2 The diagram shows the limiting oxygen index of each sample, where solid circles represent examples and hollow rhombuses represent comparative examples.

[0031] Figure 3 The image shows the residual layer integrity rate of each sample after treatment at 950°C. Solid circles represent examples, and hollow rhombuses represent comparative examples.

[0032] Figure 4 The image shows the center temperature of the unexposed surface of each sample after being exposed to a hot surface at 900°C for 10 minutes. Solid circles represent examples, and hollow rhombuses represent comparative examples.

[0033] Figure 5 Fourier transform infrared spectra comparison of ethylene-ethyl acrylate-maleic anhydride terpolymer, modified elastic precursor, and modified elastic intermediate with moderate borylation level. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0035] Ethylene-vinyl acetate copolymer: Dow, brand name ELVAX™ 260. The nominal parameters used in the examples are: vinyl acetate mass fraction 28%, melt flow rate 6 g / 10 min (190 °C, 2.16 kg), density 0.955 g / cm³. 3 The DSC melting peak temperature is 75℃. Ethylene-ethyl acrylate-maleic anhydride terpolymer: SK Functional Polymer, brand name LOTADER 4700. The nominal parameters used in the examples are: ethyl acrylate mass fraction 29%, maleic anhydride mass fraction 1.3%, melt flow rate 7 g / 10 min (190 °C, 2.16 kg), DSC melting peak temperature 65 °C. Hydroxyl-terminated polydimethylsiloxane: Gelest, Inc., trade name DMS-S15, Example 25°C kinematic viscosity 65 mmHg 2 / s, hydroxyl equivalent 0.60 eq / kg; Aluminum hydroxide: Al(OH)3 mass fraction approximately 99.4%, moisture content not exceeding 0.35% at 105℃; the example uses a d50 of 1.9 μm and a BET specific surface area of ​​4 m². 2 / g; Quartz powder: SiO2 mass fraction not less than 99.0%, the example uses d10 of 4μm, d50 of 23μm, d90 of 60μm, and true density of 2.65g / cm³. 3 .

[0036] Long needle-shaped wollastonite: The examples used an average particle size of 10.3 μm and an aspect ratio of 15:1.

[0037] Preparation Example 1: Modified Elastic Precursor Step (1): Add 90.00g of ethylene-ethyl acrylate-maleic anhydride terpolymer and 540mL of anhydrous xylene to the reaction apparatus, purge with nitrogen, stir at 350r / min, and maintain at 100℃ for 40min to obtain a uniform thermal dispersion. Add 1.80g of 3-aminopropyltriethoxysilane dropwise over 20min, and continue stirring at 100℃ for 2.5h from the end of the dropwise addition.

[0038] Step (2): Add 38.00g of hydroxyl-terminated polydimethylsiloxane and 0.140g of tetrabutyl titanate; raise the system to 110°C within 30min, stir under nitrogen flow for 4h and continuously remove the ethanol fraction; stop heating when no visible distillate is seen for 30min and cool down to 85°C.

[0039] Step (3): Add the thermal dispersion obtained in step (2) to 2.00 L of acetone within 15 min, stir for 30 min and then filter; wash the filter cake with 480 mL of acetone each time, for a total of 3 washes. Dry the filter cake at 60 °C and 10 kPa for 10 h to obtain 118.72 g of modified elastic precursor.

[0040] Preparation Example 2: Modified Elastic Intermediate with Moderate Boration Level Step (1): Weigh 60.00 g of the elastic precursor obtained in Preparation Example 1, add 420 mL of anhydrous xylene, and stir for 30 min at 95 °C and 350 r / min to obtain a thermal dispersion. Add 0.250 g of boric acid that has passed through a 100-mesh sieve to the thermal dispersion, raise the temperature to 110 °C within 30 min, remove the azeotropically reacted water and maintain the temperature for 4 h.

[0041] Step (2): After cooling the system to 90℃, hot filter was performed to remove unreacted boric acid and insoluble matter. The hot filtrate was added to 2.00L of acetone, stirred for 30min, and then filtered. The filter cake was washed with 240mL of acetone each time, for a total of 3 washes. The filter cake was dried at 60℃ and 10kPa for 10h, crushed, and the particles that passed through a 4mm sieve and remained on a 2mm sieve were collected to obtain 58.42g of modified elastic intermediate with a moderate borylation level.

[0042] Preparation Example 3: Modified Elastic Intermediate with Low Boration Level Except for changing the amount of boric acid in step (1) of Preparation Example 2 to 0.180g, the other raw materials, amounts and operating conditions were the same as in Preparation Example 2, and 58.53g of modified elastic intermediate with low borylation level was obtained.

[0043] Preparation Example 4: Modified Elastic Intermediate with High Boration Level Except for changing the amount of boric acid in step (1) of Preparation Example 2 to 0.320g, the other raw materials, amounts and operating conditions were the same as in Preparation Example 2, and 58.30g of modified elastic intermediate with high borylation level was obtained.

[0044] Example 1 Step (1): Set the internal mixer to 95°C and 50 r / min, add 115.00 g of ethylene-vinyl acetate copolymer, and plasticize for 3 min; add 15.00 g of the modified elastic intermediate with a medium borylation level obtained in Preparation Example 2, and continue mixing for 4 min.

[0045] Step (2): Premix 32.00g aluminum hydroxide, 48.00g quartz powder, 16.00g long needle-shaped wollastonite, 0.65g antioxidant 1010 and 1.00g zinc stearate evenly, and divide into 3 portions, each 32.55g. Add the 3 portions of premix to the internal mixer in sequence, with an interval of 1.5min between two adjacent additions; after the third portion is added, continue mixing for 8min, and discharge the material when the temperature reaches 120℃.

[0046] Step (3): The mixture is fed into a co-rotating twin-screw extruder. The temperatures of the four barrel zones are 105℃, 115℃, 125℃ and 125℃ respectively. The screw speed is 80 r / min and the feed rate is 2.5 kg / h. After air cooling, the extruded strip is granulated. The particles that pass through a 4 mm sieve and remain on a 2 mm sieve are collected to obtain 222.64 g of heat-insulating and fire-resistant cable material.

[0047] Example 2 Except for changing the amount of ethylene-vinyl acetate copolymer in step (1) of Example 1 to 110.00g and changing the amount of modified elastic intermediate with medium borylation level obtained in Preparation Example 2 to 20.00g, the other raw materials, amounts and preparation conditions are the same as in Example 1, and 222.41g of heat-insulating and fireproof cable material is obtained.

[0048] Example 3 Except for changing the amount of ethylene-vinyl acetate copolymer in step (1) of Example 1 to 105.00g and changing the amount of modified elastic intermediate with medium borylation level obtained in Preparation Example 2 to 25.00g, the other raw materials, amounts and preparation conditions are the same as in Example 1, and 221.98g of heat-insulating and fireproof cable material is obtained.

[0049] Example 4 Except for replacing the modified elastic intermediate with a medium borylation level used in Example 2 with 20.00g of the modified elastic intermediate with a low borylation level obtained in Preparation Example 3, the other raw materials, amounts and preparation conditions were the same as in Example 2, and 222.50g of heat-insulating and fire-resistant cable material was obtained.

[0050] Example 5 Except for replacing the modified elastic intermediate with a medium borylation level used in Example 2 with 20.00g of the modified elastic intermediate with a high borylation level obtained in Preparation Example 4, the other raw materials, amounts and preparation conditions were the same as in Example 2, and 222.18g of heat-insulating and fire-resistant cable material was obtained.

[0051] Comparative Example 1: Following the dry basis feed ratios of Preparation Example 1 and Preparation Example 2, and normalizing to 20.00 g, 13.79 g of ethylene-ethyl acrylate-maleic anhydride terpolymer, 5.82 g of hydroxyl-terminated polydimethylsiloxane, 0.28 g of 3-aminopropyltriethoxysilane, 0.02 g of tetrabutyl titanate, and 0.09 g of boric acid were directly added to the internal mixing system of Example 2, replacing the 20.00 g of the modified elastic intermediate with a moderate borylation level in Example 2. These five materials were added sequentially after the ethylene-vinyl acetate copolymer was plasticized for 3 min and then mixed for 4 min. The remaining raw materials, amounts, and preparation conditions were the same as in Example 2, yielding 221.70 g of heat-insulating and fire-resistant cable material.

[0052] Comparative Example 2: Except that the 20.00g modified elastic intermediate with medium borylation level in Example 2 was replaced with 20.00g modified elastic precursor obtained in Preparation Example 1, the other raw materials, amounts and preparation conditions were the same as in Example 2, and 222.36g of heat-insulating and fireproof cable material was obtained.

[0053] Comparative Example 3: An intermediate was prepared according to the method of Preparation Example 2, except that the amount of boric acid was changed from 0.250 g to 0.150 g, resulting in 58.56 g of modified elastic intermediate below the lower boric acid level. Except for replacing the 20.00 g of the low borylation level intermediate in Example 4 with 20.00 g of this intermediate, the other raw materials, amounts, and preparation conditions were the same as in Example 4, yielding 222.28 g of heat-insulating and fire-resistant cable material.

[0054] Comparative Example 4: An intermediate was prepared according to the method of Preparation Example 2, except that the amount of boric acid was changed from 0.250 g to 0.350 g, resulting in 58.18 g of modified elastic intermediate above the upper point of boric acid. Except that 20.00 g of this intermediate was used to replace the 20.00 g of high borylation level intermediate in Example 5, the other raw materials, amounts, and preparation conditions were the same as in Example 5, resulting in 221.95 g of heat-insulating and fire-resistant cable material.

[0055] Comparative Example 5: Except that the amount of modified elastic intermediate with medium borylation level in Example 1 was changed from 15.00g to 12.00g, and the amount of ethylene-vinyl acetate copolymer was changed from 115.00g to 118.00g, the other raw materials, amounts and preparation conditions were the same as in Example 1, and 222.72g of heat-insulating and fire-resistant cable material was obtained.

[0056] Comparative Example 6: Except that the amount of modified elastic intermediate with medium borylation level in Example 3 was changed from 25.00g to 28.00g, and the amount of ethylene-vinyl acetate copolymer was changed from 105.00g to 102.00g, the other raw materials, amounts and preparation conditions were the same as in Example 3, and 221.56g of heat-insulating and fireproof cable material was obtained.

[0057] Performance testing Specialized sample preparation and conditioning for testing: Except for acetone extractables and melt flow rate, which were tested directly using granules, all other tests used compressed samples. Each sample granule was dried at 60℃ and 10kPa for 6 hours, then added to a mold preheated to 135℃. After preheating without pressure for 5 minutes, it was hot-pressed at 10MPa for 5 minutes, and then water-cooled to 35℃ while maintaining pressure before demolding. Tensile tests used 2.0mm thick sheets, limiting oxygen index and fire residue tests used 4.0mm thick sheets, and back-exposed surface temperature tests used 6.0mm thick sheets. After compression, the samples were conditioned for 48 hours at 23±2℃ and 50±5% relative humidity.

[0058] Acetone extractable: Weigh 2.000 g of cable material granules dried at 60℃ and 10 kPa for 6 h, place them in a Soxhlet extractor, and extract continuously with 150 mL of acetone for 6 h. Remove the sample and dry it at 60℃ and 10 kPa until the difference between two consecutive weighings is no greater than 0.002 g. The acetone extractable is calculated as (dry weight before extraction - dry weight after extraction) / dry weight before extraction × 100%. Each sample is tested in triplicate, and the arithmetic mean is taken.

[0059] Tensile properties: According to GB / T1040.2-2022, 2.0 mm thick sheets were cut into 1BA type specimens, and tensile strength and elongation at break were determined at 23±2℃ and a test speed of 50 mm / min. Five specimens were tested for each sample, and the arithmetic mean was taken.

[0060] Melt mass flow rate: The melt mass flow rate of cable material particles was determined according to GB / T3682.1-2018 at 190℃ and 2.16kg, with preheating for 5min after loading. Each sample was tested in triplicate, and the arithmetic mean was taken.

[0061] Limiting oxygen index: According to GB / T2406.2-2009, 4.0 mm tablets were cut into 100 mm × 10 mm × 4 mm type I specimens, and the limiting oxygen index was determined by top-side ignition. Three samples were tested in parallel for each specimen, and the arithmetic mean was taken.

[0062] Bending strength of residual layer at 950℃: 4.0mm sheet was cut into strips of 80mm×10mm×4mm and placed in a box furnace. The temperature was increased to 950℃ at 10℃ / min and held for 30min. Afterward, it was cooled in the furnace to 200℃ and then removed and cooled in air to 23℃. A three-point bending test was performed using a universal testing machine with a span of 40mm and a loading speed of 0.5mm / min. Bending strength was calculated as 3FL / (2bh) 2 The calculation is performed, where F is the maximum load, L is the span, b is the specimen width, and h is the specimen thickness. Five specimens are tested for each sample, and the arithmetic mean is taken.

[0063] Integrity rate of residual layer at 950℃: Cut 4.0mm tablets into 50mm×50mm×4mm samples, hold at 950℃ for 30 minutes according to the aforementioned heating procedure, and then cool. Weigh the mass of the intact residual layer (m1). Drop the residual layer face down from a height of 500mm onto a 10mm thick flat steel plate, repeating this process three times. Collect all fragments and pass them through a 5mm square-hole sieve. Weigh the mass of the fragments remaining on the sieve (m2). The integrity rate of the residual layer is calculated as m2 / m1×100%. Three samples were tested in parallel for each sample, and the arithmetic mean was taken.

[0064] Center temperature of the unexposed surface: Cut a 6.0mm sheet into 100mm×100mm×6mm test plates. Using a box-type high-temperature furnace with an 80mm circular radiant aperture, after the furnace temperature stabilizes at 900±20℃, fix the test plate on the outside of the radiant aperture, with the hot side of the test plate 30mm away from the inner wall of the furnace cavity, and seal the perimeter with ceramic fiber. Attach a K-type thermocouple to the center of the unexposed surface and record the temperature continuously for 10 minutes, taking the center temperature of the unexposed surface at 10 minutes. Perform parallel tests on 3 pieces for each sample and take the arithmetic mean.

[0065] Fourier transform infrared spectroscopy: Following the general principles of GB / T6040-2019, ethylene-ethyl acrylate-maleic anhydride terpolymer, the modified elastic precursor obtained in Preparation Example 1, and the modified elastic intermediate with a moderate borylation level obtained in Preparation Example 2 were used as test samples. Each sample was dried at 60℃ and 10 kPa for 6 h; spectrally pure potassium bromide was dried at 110℃ for 4 h and cooled in a desiccator. The sample and potassium bromide were then ground at a mass ratio of 1:100 for 5 min, and pressed into a pellet at 10 MPa for 1 min. Transmission mode was used, with a scanning range of 4000–400 cm⁻¹. -1 The resolution is 4cm. -1A total of 32 scans were performed.

[0066] Table 1. Intermediate state, mechanical properties, processability, and fire-damaged residual layer strength of each sample.

[0067] Example 2 and Comparative Example 1 had the same total organic component dosage, inorganic filler dosage, and cable material formation conditions. The difference was that in Example 2, the elastic intermediate was formed and washed independently first, while in Comparative Example 1, a terpolymer, hydroxyl-terminated polydimethylsiloxane, 3-aminopropyltriethoxysilane, tetrabutyl titanate, and boric acid were directly added in the same dry basis feed ratio. In Example 2, the acetone extractable content decreased from 4.12% in Comparative Example 1 to 0.82%, the tensile strength increased from 7.63 MPa to 10.05 MPa, and the elongation at break increased from 136.2% to 228.0%. This indicates that pre-forming, washing, and subsequent addition of the elastic intermediate helps reduce free low-molecular-weight silica components and improves stress transfer and tensile elongation of the highly filled system.

[0068] In terms of fire resistance, the flexural strength of the residual layer at 950°C in Example 2 increased from 1.59 MPa to 3.12 MPa compared to Comparative Example 1, the integrity rate of the residual layer increased from 45.9% to 82.6%, and the center temperature of the unexposed surface after being exposed to the hot surface at 900°C for 10 minutes decreased from 339°C to 271°C.

[0069] The only difference between Example 2 and Comparative Example 2 is whether or not the independently collected elastic precursor is partially borated. In Example 2, the flexural strength of the residual layer at 950°C increased from 1.98 MPa to 3.12 MPa compared to Comparative Example 2, the residual layer integrity increased from 58.7% to 82.6%, and the center temperature of the unexposed surface decreased from 319°C to 271°C; simultaneously, the tensile strength remained within the range of 9.84~10.05 MPa. These results indicate that partial boration after the formation of the elastic precursor is beneficial for improving the structural integrity and thermal insulation of the fire-exposed residual layer, while retaining room-temperature tensile strength.

[0070] Example 4 and Comparative Example 3 differed only in the amount of boric acid used in preparing 60.00g of the elastic precursor, to 0.180g and 0.150g, respectively. After increasing the amount of boric acid from 0.150g to 0.180g, the flexural strength of the residual layer at 950℃ increased from 2.36MPa to 2.73MPa, the integrity rate of the residual layer increased from 67.9% to 76.1%, and the center temperature of the unexposed surface decreased from 302℃ to 284℃. This indicates that when the amount of boric acid is less than 0.180g, the bonding and insulation of the fire-exposed residual layer are insufficient.

[0071] Example 5 and Comparative Example 4 differed only in the amount of boric acid used in preparing 60.00g of the elastic precursor, to 0.320g and 0.350g, respectively. Increasing the boric acid content from 0.320g to 0.350g resulted in a decrease in elongation at break from 207.0% to 176.0%, a decrease in the flexural strength of the residual layer at 950℃ from 3.42MPa to 2.94MPa, and a decrease in the integrity of the residual layer from 87.8% to 79.6%. These results indicate that further increasing the boric acid content increases the material's tendency for room temperature deformation to be limited and for the residual layer to crack after firing. 0.320g represents a good balance between residual layer strength and flexibility.

[0072] In Example 1 and Comparative Example 5, only the amount of elastic intermediate was changed, and the total polymer mass was kept at 130.00 g by adjusting the amount of ethylene-vinyl acetate copolymer accordingly. After increasing the amount of intermediate from 12.00 g to 15.00 g, the elongation at break increased from 161.0% to 194.2%, the flexural strength of the residual layer at 950°C increased from 2.18 MPa to 2.64 MPa, and the integrity of the residual layer increased from 61.3% to 72.8%. This indicates that when the amount of intermediate is less than 15.00 g, both room temperature elongation and the retention of the residual layer after ignition are insufficient.

[0073] Example 3 and Comparative Example 6 only changed the amount of elastic intermediate, while keeping the total polymer mass at 130.00 g. When the intermediate amount was increased from 25.00 g to 28.00 g, the limiting oxygen index increased from 30.0% to 30.3%, and the residual layer integrity increased from 86.9% to 88.5%. However, the tensile strength decreased from 9.36 MPa to 8.54 MPa, and the melt flow rate decreased from 2.73 g / 10 min to 2.08 g / 10 min. These results indicate that above 25.00 g, the fire-resistant properties only continued to change slightly, while the room temperature strength and melt flowability further decreased. 25.00 g represents the upper limit of overall performance.

[0074] In Examples 1-3, the amounts of the medium-boronized elastic intermediate were 15.00 g, 20.00 g, and 25.00 g, respectively. With increasing intermediate content, the elongation at break increased from 194.2% to 252.0%, the limiting oxygen index increased from 28.8% to 30.0%, and the center temperature of the unfired surface decreased from 294°C to 259°C; the melt flow rate decreased from 3.58 g / 10 min to 2.73 g / 10 min. This demonstrates that a dosage range of 15.00–25.00 g can cover different balance points between flexibility, the formation of a refractory layer, and processing fluidity.

[0075] Examples 4, 2, and 5 used 0.180 g, 0.250 g, and 0.320 g of boric acid, respectively, to prepare elastic intermediates. With increasing boric acid content, the flexural strength of the residual layer at 950°C increased from 2.73 MPa to 3.42 MPa, the residual layer integrity increased from 76.1% to 87.8%, while the elongation at break decreased from 239.2% to 207.0%. These results indicate that the amount of boric acid used (0.180–0.320 g) can balance the strength of the fire-exposed residual layer with its room-temperature ductility by adjusting the borylation level in different portions.

[0076] Figure 5 In the middle, the ethylene-ethyl acrylate-maleic anhydride terpolymer at 1728 cm⁻¹ -1 There is a strong absorption near the ester carbonyl group, and at 1836 cm⁻¹ -1 and 1772cm -1 There is a weak anhydride carbonyl-related absorption nearby. After forming the modified elastic precursor, the absorption is 1836 cm⁻¹. -1 and 1772cm -1 The weak absorption related to the carbonyl group of the nearby anhydride relative to 1728 cm⁻¹ -1 The absorption of the nearby copolymer ester carbonyl group is weakened, while the 1256 cm⁻¹ is also reduced. -1 1090~1020cm -1 and 804cm -1 The enhanced overall absorption associated with the nearby silica-oxygen chains indicates that the resulting elastic precursor retains ethylene copolymer segments and introduces structural units that can be identified by the silica-oxygen chain feature regions.

[0077] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A heat-insulating and fire-resistant cable material, characterized in that, By weight, it includes the following raw materials: 105-115 parts of ethylene-vinyl acetate copolymer; 15-25 parts of modified elastic intermediate; 30-34 parts aluminum hydroxide; 46-50 parts of quartz powder; 14-18 parts of long needle-shaped wollastonite; 0.5~0.8 parts of antioxidant 1010; 0.8~1.2 parts zinc stearate; The method for preparing the modified elastic intermediate includes: First, the ethylene-ethyl acrylate-maleic anhydride terpolymer is reacted with 3-aminopropyltriethoxysilane, and then condensed with hydroxyl-terminated polydimethylsiloxane under the catalysis of tetrabutyl titanate to obtain the modified elastic precursor. The modified elastic precursor is subjected to a borylation reaction with boric acid, and the resulting reaction product is subjected to hot filtration, precipitation, washing and drying to obtain the modified elastic intermediate.

2. The heat-insulating and fire-resistant cable material according to claim 1, characterized in that, The mass ratio of the ethylene-ethyl acrylate-maleic anhydride terpolymer, 3-aminopropyltriethoxysilane, hydroxyl-terminated polydimethylsiloxane, and tetrabutyl titanate is 90:1.7~1.9:36~40:0.12~0.

16.

3. The heat-insulating and fire-resistant cable material according to claim 1, characterized in that, Based on 60 parts of the modified elastic precursor, the amount of boric acid used is 0.18 to 0.32 parts.

4. A method for preparing a heat-insulating and fire-resistant cable material according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Add the ethylene-vinyl acetate copolymer to a mixer for plasticizing, add the modified elastic intermediate, and continue mixing to obtain a polymer mixture; (2) Aluminum hydroxide, quartz powder, long needle-shaped wollastonite, antioxidant 1010 and zinc stearate are premixed evenly, the resulting premix is ​​divided into 3 equal parts and added to the polymer mixture in sequence, and after further mixing, the mixture is discharged to obtain the mixture. (3) The mixture is fed into a co-rotating twin-screw extruder for melt extrusion. The extruded strip is cooled and pelletized to obtain the heat-insulating and fire-resistant cable material.

5. The preparation method according to claim 4, characterized in that, In step (1), the set temperature of the internal mixer is 90~100℃ and the rotor speed is 45~55r / min; the plasticizing time of the ethylene-vinyl acetate copolymer is 2~4min, and the mixing time after adding the modified elastic intermediate is 3~5min.

6. The preparation method according to claim 4, characterized in that, In step (2), the feeding interval between two adjacent premixes is 1-2 min, the mixing time after the third premix is ​​added is 6-10 min, and the material temperature at discharge is 118-122℃.

7. The preparation method according to claim 4, characterized in that, In step (3), the temperatures of the four barrel temperature zones of the co-rotating twin-screw extruder are 100~110℃, 110~120℃, 120~130℃ and 120~130℃ respectively, the screw speed is 70~90r / min, and the feed rate is 2~3kg / h.

8. The preparation method according to claim 4, characterized in that, In step (3), the extrusion strip is air-cooled and then granulated, and the granules that pass through a 4mm sieve and remain on a 2mm sieve are collected.